A Case Study of Form Four Students' Understanding of Angles in Circles - Mazma Syahidatul Ayuni, Mazlan (Universiti Malaysia Sarawak, (UNIMAS), 2008)
Mathematics is a compulsory subject both in the primary and secondary school curriculum in Malaysia. The National Philosophy of Education and Malaysia's Vision 2020 aim to produce a new generation of Malaysians who are able to think critically, systematically and who are able to use their knowledge of mathematics to meet new challenges in this fast changing world. From here, we can see the importance of mathematics and its influence in the progress of a nation. This study was conducted to investigate Form Four students' understanding of angles in circles. The samples used in this study consisted of eight Form Four students from one school in Kuching district. A set of six mathematical questions was given to each student to solve. Verbal protocol which is a common method in cognitive task analysis was chosen as the technique of data collection in this study. The audio-recorded data collected were analysed together with the data from interviews and students' written answers. From the analysis, 19 conceptual knowledge and 8 procedural knowledge were identified. Six students' models were constructed based on the conceptual knowledge and procedural knowledge. All the students were able to answer the questions. However, both the audio and written answers showed that some students have misconceptions of angles in circles. The findings of this study can be used to enhance teaching and learning of mathematics.